The Networked Data Lab: What linked data can tell us about the elective care waiting list in the UK - Prendergast, Tom; Knight, Hannah; Barr, Benjamin; Butler, Jessica; Chan, Jodie; Daras, Konstantinos; Elvidge-Murgatroyd, Josh; Palczewska, Anna; Popham, Frank; Yarwood, Marcus (International Journal of Population Data Science, 2026)
Existing research on NHS elective care backlogs in the UK predominantly focuses on aggregate waiting list figures. Until recently there has been little analysis that uses patient-level data to disaggregate the waiting list, or which uses linked data to take a system-wide view. Through the Health Foundation’s Networked Data Lab, analytical teams in four areas of the UK linked data on elective care waiting times to primary and secondary healthcare datasets to examine inequalities in waiting times and the impact of waiting on health, with the aim of identifying the most productive points for intervention, support and service improvement. We examined how waiting times for elective care and reasons for waitlist pathways ending differed between demographic groups and treatment specialties. We also created counts and rates of unplanned healthcare use for individuals who waited for elective care in the months before they joined the waiting list, while waiting for care, and after treatment. Results include: Patients living in deprived areas tend to wait longer than those living in more affluent areas, and people of Asian, Black or mixed backgrounds had longer median wait times than white patients. People living in more deprived areas had higher rates of A&E attendances than people from more affluent areas while waiting, and more frequently had pathways end due to missed appointments. Rates of unplanned healthcare use are often higher before and after waiting than during the wait itself. People who waited for longer had greater relative increases in healthcare use following treatment.